EFFECT OF WORK COMPENSATION AND MOTIVATION TOWARDS PRODUCTIVITY OF WORKERS (A SURVEY IN PT. NECIS INDAH CEMERLANG BANDUNG) - Komar Priatna, Deden; Devia Indriyani; Winna Roswinna (Dinasti International Journal of Management Science, 2020)
To increase profits for companies, a highly motivated workforce is needed, profit will increase if supported by good work productivity of workers. The achievement of these objectives depends on the policies adopted by the company. But on the other hand, the work productivity of workers decreases, this is due to low work motivation and the relative compensation of only enough for the basic needs of the lives of workers, this results in targeted production not being achieved according to targets set by the company, as for the goals. This study aims to determine (1) compensation provided by PT. Necis Indah Cemerlang Bandung, (2) motivation of workers at PT. Necis Indah Cemerlang Bandung, (3) work productivity at PT. Necis Indah Cemerlang Bandung, and (4) the effect of compensation and motivation both jointly and individually on work productivity at PT. Necis Indah Cemerlang Bandung. The method used is descriptive and expansive survey method of the analysis unit of the workers of PT. Necis Indah Cemerlang Bandung. Sampling using a random sampling method and simple with a sample of (n) 85 workers. The type of investigation into this study is causality, and the time horizon in this study is cross-sectional and the analytical method used is frequency distribution and path analysis. The findings of this study are compensation and motivation both jointly and individually influencing work productivity workers at PT. Necis Indah Cemerlang Bandung, but partially dominant motivation affects work productivity rather than compensation